THE EFFECT OF EMPLOYEE CREATIVITY ON INNOVATIVE WORK BEHAVIOR: THE MODERATING ROLE OF WORK CENTRALITY - Anak Agung Istri Intan Prabawati; I Gede Riana (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to analyze the effect of employee creativity on innovative work behavior with the moderating role of work centrality. The research sample consisted of 38 employees at a Military Court Office III-14 Denpasar. Data were collected using a closed-ended questionnaire based on a 5-point Likert scale and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach with the assistance of WarpPLS software. The results indicate that employee creativity has a positive and significant effect on innovative work behavior. Work centrality was found to positively moderate this relationship, strengthening the influence of creativity on employee innovation. These findings confirm the Job Demands-Resources (JD-R) Theory, where creativity and work centrality function as personal resources that promote positive work behavior. The practical implication highlights the importance for organizations to foster a work environment that supports creativity and work meaningfulness. Future research is recommended to research expand the sample and apply a mixed-methods approach.